Solidification, microstructure and mechanical properties of Mg-2.8Nd-1.5Gd-0.5Zn-0.5Zr cast alloy with erbium addition - Ahmad, R.; Elaswad, A.M.M.; Hamzah, M. Z.; Shahizan, N. R. (EDP Sciences, 2018)
The thermal parameters of Mg-2.8Nd-1.5Gd-0.5Zn-0.5Zr cast alloy with 0.25 wt.% of erbium (Er) were evaluated by the computer-aided cooling curve thermal analysis(CA CCTA), whereas the microstructure analysis was investigated by the optical microscope and scanning electron microscopy. Results from the cooling curve and microstructure analysis showed that Er altered the grain size of the alloys. In addition, the grain size was reduced by approximately 19.6% with the addition of Er. Scanning electron microscopy results showed that Er formed an Mg-Zn-Nd-Er phase which distributed along the grain boundaries. Furthermore, the mechanical properties were investigated by hardness and tensile tests with Er addition. The addition of 0.25 wt.% of Er significantly improved the ultimate tensile strength and yield strength. In addition, the hardness value of Mg-2.8Nd-1.5Gd-0.5Zn-0.5Zr increased by 13.9% with Er addition.